Hubungan antara Infeksi Protozoa Cryptosporidium Sp dengan Kejadian Diare Kronis pada Pasien HIV/AIDS di RSUD Dr. Moewardi Surakarta - Primawati, Surya Dewi; Dirgahayu, Paramasari; Haryoputro, Dani Redhono (Nexus Biomedika, 2014)
Background: Cryptosporidium sp. is apicomplexan parasite that causes chronic diarrhea. This parasiteâs infection can cause high mortality in immunocompromais individuals especially who are infected with HIV/AIDS. Although the HIV/AIDS infection is a concern in Indonesia, but there has been no study on the infection of chronic diarrhea in patients with HIV/AIDS. This study aimed to know the correlation between the Protozoan Cryptosporidium sp. infection and chronic diarrhea incident in patients with HIV/AIDS at Dr. Moewardi Hospital Surakarta. Methods: This was an observational analytic study using cross sectional approach conducted on May â September 2013. Thirty six patients with HIV/AIDS at Dr. Moewardi Hospital that were appropriate with the criteria of restriction were taken for samples. The data about chronic diarrhea, age, gender, level of education were obtained from the questionnaire. Identification of Cryptosporidium sp. in stool was examined using modified acid fast stain techniques, while their consistency were obtained through macroscopic examination. Data about the status of patients CD4 were obtained from the medical record. The correlation between chronic diarrhea, sex, level of education, consistency of the stool, CD4 status and Cryptosporidium sp. infection was analyzed by using Fisher Test (a=0.05). Results: Fisher test analysis showed there was no significant correlation between infection of Cryptosporidium sp. and incidence of chronic diarrhea (p = 1). Analysis of correlation between gender, level of education, consistency of the stool, CD4 status and Cryptosporidium sp. infection, the value of p > 0.05 was obtained. Conclusions: There was no significant correlation between Cryptosporidium sp.Â  infection and chronic diarrhea incident in patients with HIV/AIDS at Dr. Moewardi Hospital Surakarta. Keyword : Cryptosporidium sp, chronic diarrhea, HIV/AIDS Â